Mathematical Processes and Modeling in Problem-Solving: Designing Learning Models for Higher-Order Thinking - Nurmawati, Nurmawati; Purnomo, Eko Andy; Dian Mawarsari, Venissa; Prihaswati, Martyana; Dwi Pamungkas, Megita; Kintoko, Kintoko (IJORER : International Journal of Recent Educational Research, 2026)
21st-century mathematics learning requires the development of Higher Order Thinking Skills (HOTS) through meaningful problem-solving and mathematical modeling. Various studies have shown that students' HOTS abilities are still in the low category, even though problem-solving models have been widely implemented. However, most existing models are still procedural and have not systematically integrated horizontal and vertical mathematization processes with mathematical modeling cycles in a single learning syntax. This study aims to develop a problem-solving learning model grounded in mathematical processes and modeling to improve students' HOTS skills. The study uses the Research and Development (R&D) approach proposed by Thiagarajan and Semmel. The developed model integrates the stages of situational orientation, horizontal mathematization, vertical mathematization, contextual interpretation, and reflection and revision in a systematic and measurable learning syntax. The validation results from nine experts showed an average score of 3.61 in the very valid category, indicating that the model meets pedagogical feasibility, mathematical substance, and evaluative criteria. The novelty of this research lies in integrating Polya's steps, the mathematization process, and the mathematical modeling cycle into a learning model explicitly designed to develop HOTS. Further research is recommended to test the model's effectiveness through experimental studies in various educational contexts to strengthen empirical evidence of its implementation.